Lineage specific transcriptional regulation of DICER by MITF in melanocytes - Levy, Carmit (2010)
DICER is a central regulator of microRNA maturation. However little is known about mechanisms regulating its expression in development or disease. While profiling miRNA expression in differentiating melanocytes, two populations were observed: some upregulated at the pre-miRNA stage, and others upregulated as “mature” miRNAs (with stable pre-miRNA levels). Conversion of pre-miRNAs to fully processed miRNAs appeared to be dependent upon stimulation of DICER expression—an event found to occur via direct transcriptional targeting of DICER by the melanocyte master transcriptional regulator MITF. MITF binds and activates a conserved regulatory element upstream of DICER’s transcriptional start site upon melanocyte differentiation. Targeted KO of DICER is lethal to melanocytes, at least partly via DICER-dependent processing of the pre-miRNA-17~92 cluster thus targeting BIM, a known pro-apoptotic regulator of melanocyte survival. These observations highlight a central mechanism underlying miRNA regulation which could exist for other cell types during development.